1995
DOI: 10.1255/jnirs.68
|View full text |Cite
|
Sign up to set email alerts
|

An Overview of Research and Development of near Infrared Spectroscopy in Japan

Abstract: This paper presents an overview of research and development of near infrared (NIR) spectroscopy in Japan. The application of NIR spectroscopy in Japan only stretches back to the early 1980s. Thus, the history is rather short, but progress in the research and development of NIR spectroscopy is extremely fast. The history and present status of NIR spectroscopy in Japan are described and a number of representative applications carried out in Japan are introduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…The correlation coefficients (rs) between the predicted and the reference data were 0.93, 0.90 and 0.84 for the contents of moisture, protein and starch, respectively. Moreover, when bias and skew were checked by the Student's t-test for the MREs, those |t| s were less than 2 (17). This finding suggests that the established MREs can be used for the determination of moisture, protein and starch in buckwheat flours.…”
Section: Resultsmentioning
confidence: 91%
“…The correlation coefficients (rs) between the predicted and the reference data were 0.93, 0.90 and 0.84 for the contents of moisture, protein and starch, respectively. Moreover, when bias and skew were checked by the Student's t-test for the MREs, those |t| s were less than 2 (17). This finding suggests that the established MREs can be used for the determination of moisture, protein and starch in buckwheat flours.…”
Section: Resultsmentioning
confidence: 91%
“…Nowadays, nondestructive techniques for quality evaluation have gained in popularity (Iwamoto, Kawano, & Ozaki, 1995;Jha & Matsuoka, 2000. These techniques, particularly for fruits and vegetables, are quick and easy to use.…”
Section: Introductionmentioning
confidence: 99%
“…When these conditions were met, however, rice scorching occurred during measurement. Other difficulties were encountered using the transmittance mode, including the need for a completely darkened cell chamber 9 , and it was concluded that transmittance spectroscopy would pose numerous constraints and thus would not be suitable for the envisioned combine-mounted device.…”
Section: Study Of Spectroscopic Modesmentioning
confidence: 99%